Investigation into the safety, and serological responses elicited by delivery of live intranasal vaccines for bovine herpes virus type 1, bovine respiratory syncytial virus, and parainfluenza type 3 in pre-weaned calves - Flynn, Anna; McAloon, Catherine; Sugrue, Katie; Fitzgerald, Ricki; Sheridan, Cara; Cowley, Bosco; McAloon, Conor; Kennedy, Emer (Frontiers in Veterinary Science, 2024)
Despite the fact that pneumonia remains a leading cause of mortality and morbidity in pre-weaned calves, relatively little is known regarding the effects of the concurrent administration of intranasal pneumonia virus vaccines, particularly in calves with high levels of maternally derived antibodies. The objective of this study was to use a cohort of 40 dairy and dairy-beef female and male calves (27 females and 13 males) to determine serological responses to concurrent administration at 3 weeks of age (22 ± 4.85 days) of two commercially available intranasal (IN) vaccines for the viruses: bovine respiratory syncytial virus (BRSV), bovine herpes virus 1 (BoHV-1), and parainfluenza-3-virus (PI3-V). The study groups were as follows: (i) Bovilis IBR Marker Live only® (IO), (ii) Bovilis INtranasal RSP Live® only (RPO), (iii) Concurrent vaccination with Bovilis IBR Marker Live® & Bovilis Intranasal RSP Live® (CV), and (iv) a control group of non-vaccinated calves (CONT). The calves’ serological response post-IN vaccination, clinical health scores, rectal temperatures, and weights were measured. Data were analyzed in SAS using mixed models and logistic regression. The CV calves had an average daily weight gain (ADG) of 0.74 (±0.02) kg, which was similar to CONT (0.77 ± 0.02 kg). Despite no significant differences in the antibody levels between study groups 3 weeks post-IN vaccination, following the administration of subsequent parenteral injections in the form of Bovilis Bovipast RSP®(antigens; inactivated BRSV, inactivated PI3-V, inactivated Mannheimia haemolytica) and Bovilis IBR Marker Live®, the antibody levels of the BRSV and PI3-V increased in both the CV and RPO study groups. Concurrent vaccination resulted in no increase in fever and no difference in health scores when compared to CONT.